The in vitro antiviral activity of an aliphatic nitro compound from Heteropteris aphrodisiaca - Melo, Fernando L.; Benati, Fabricio J.; Roman, Walter Antonio [UNESP]; Palazzo de Mello, Joao Carlos; Nozawa, Carlos; Carvalho Linhares, Rosa Elisa (Elsevier Gmbh, Urban & Fischer Verlag, 2008)
We investigated the antiviral activity of an aliphatic nitro compound (NC) isolated from Heteropteris aphrodisiaca O. Mach. (Malpighiaceae), a Brazilian medicinal ptant. The NC was tested for its antiviral activity against poliovirus type 1 (PV-1) and bovine herpes virus type 1 (BHV-1) by plaque reduction assay in cell culture. The NC showed a moderate antiviral activity against PV-1 and BHV-1 in HEp-2 celts, and the 50% inhibitory concentration (IC50) were 22.01 mu g/ml (selectivity index (SI) = 2.83) and 21.10 mu g/mi (SI = 2.95), respectivety. At the highest concentration of the drug (40 mu g/ml) a reduction of approximately 80% in plaque assay was observed for both viruses. The treatment of cells or virus prior to infection did not inhibit the replication of virus strains. (C) 2006 Elsevier GmbH. All rights reserved.
Keywords: Heteropteris ophrodisiaca; aliphatic nitro compound; poliovirus; antiviral activity; bovine herpesvirus